2018
DOI: 10.1371/journal.pgen.1007695
|View full text |Cite
|
Sign up to set email alerts
|

INDUCER OF CBF EXPRESSION 1 is a male fertility regulator impacting anther dehydration in Arabidopsis

Abstract: INDUCER OF CBF EXPRESSION 1 (ICE1) encodes a MYC-like basic helix-loop-helix (bHLH) transcription factor playing a critical role in plant responses to chilling and freezing stresses and leaf stomata development. However, no information connecting ICE1 and reproductive development has been reported. In this study, we show that ICE1 controls plant male fertility via impacting anther dehydration. The loss-of-function mutation in ICE1 gene in Arabidopsis caused anther indehiscence and decreased pollen viability as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 127 publications
(176 reference statements)
0
41
0
1
Order By: Relevance
“…mir167a and mARF8 pollen had slightly decreased viability and in vitro germination rate, similarly to pollen from inadequately desiccated ice1 mutant anthers (Wei et al, 2018). Delayed desiccation of the anther and its pollen might also delay pollen maturation, or alternatively allow pollen to bypass desiccation and dormancy, as suggested by the occasional pollen germination we observed in mARF8 anthers.…”
Section: Mir167 Limits Anther Growthmentioning
confidence: 65%
See 2 more Smart Citations
“…mir167a and mARF8 pollen had slightly decreased viability and in vitro germination rate, similarly to pollen from inadequately desiccated ice1 mutant anthers (Wei et al, 2018). Delayed desiccation of the anther and its pollen might also delay pollen maturation, or alternatively allow pollen to bypass desiccation and dormancy, as suggested by the occasional pollen germination we observed in mARF8 anthers.…”
Section: Mir167 Limits Anther Growthmentioning
confidence: 65%
“…Prolonged hydration might also delay cell wall breakdown in the septum and/or stomium through regulatory pathways regulated by cytoplasmic or apoplastic water potential. Other factors needed for dehiscence such as stomatal differentiation or lignification (Yang et al, 2007;Wei et al, 2018) were apparently unaffected in miR167 pathway mutants. Changes in growth rate are also important for developmental events such as sperm release from pollen, where peptide signals from the female gametophyte induce growth imbalance leading to pollen tube rupture and sperm release (Ge et al, 2017).…”
Section: Anther Growth Restriction Primes Anther Dehiscencementioning
confidence: 98%
See 1 more Smart Citation
“…For instance, following up on these data (Adrian et al, 2015) led to identification of the stomatal lineage-specific CYCLIN D7;1 (CYCD7;1), which is part of a system that ensures GMCs divide onceand only onceto produce a pair of GCs (Weimer et al, 2018; and further elaborated in Han et al, 2018). A role for ICE1 in anther dehydration regulation was revealed by over-representation of GC-expressed genes among ICE1-regulated genes in anthers (Wei et al, 2018). GC cell walls are unique among Arabidopsis cells with regards to the composition and modification of cell wall matrix polymers; the stomatal lineage transcriptional map was noted as a valuable resource for identification of GC-specific cell wall-modifying enzymes (Rui et al, 2018).…”
Section: Stomata Lineage Regulators: Cell-cell Signalingmentioning
confidence: 99%
“…However, it was not clear which polyamine pathway gene acts on PtrICE1 to regulate polyamine level [24]. In the process of plants responding to cold, ICE1 plays a critical role in response to environmental changes by positively regulating genes through binding speci cally to the MYC element in the promoter region which is considered as a classical mode of action on ICE1 [20,36]. Our results of BrrADC2.2 and BrrICE1.1 transgenic and RNAi roots showed that the increase of putrescine content by overexpression of BrrICE1.1 was mainly due to the binding of BrrICE1.1 to the MYC element of BrrADC2.2 promoter region in turnip (Fig.…”
Section: Brrice11 Directly Binding To the Brradc22 Promoter Regulatmentioning
confidence: 99%